THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) AND SERVICE QUALITY ON CUSTOMER LOYALTY OF BANK SYARIAH INDONESIA (BSI) - Muslim Marpaung; Ricca Hendarti; Mutiah Khaira Sihotang; Uswah Hasanah; M. Satrya Mutthaqin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research aims to determine and analyze the influence of corporate social responsibility and service quality on customer loyalty at Bank Syariah Indonesia Sukaramai Medan Branch. This research uses a quantitative method with an associative approach which aims to analyze the problem of the relationship between one variable and other variables. In this research, the respondents studied were customers of Bank Syariah Indonesia, Sukaramai Medan Branch, with a total sample of 286 people and the samples were taken using a random sampling technique. The research results show that corporate social responsibility (CSR) has a significant effect on customer loyalty with a value of tcount > t table 3,897 > 1.652, a significant value of 0.000 < 0.05, meaning that the CSR variable partially has a positive and significant effect on customer loyalty. Service quality has a significant effect on customer loyalty with Tcount > Ttable or 1.729 > 1.652, a significant value of 0.003 < 0.05 means that the service quality variable partially has a positive and significant effect on Customer Loyalty. Corporate social responsibility (CSR) and service quality simultaneously influence customer loyalty at Bank Syariah Indonesia Sukaramai Medan Branch with a significance value of 0.000 < 0.05 and a calculated F value of 8.713 > F table 3.04, meaning that there is an influence of CSR and service quality on loyalty. customers at Bank Syariah Indonesia.